Prevalence of Sensorineural Hearing Loss in Patients with Congenital Hypothyroidism in Qazvin, Iran (2015) - Fatemeh Saffari; Mohammad Hassan Nikpendar; Neda Esmailzadehha; Sonia Oveisi; Ali Homaei; Shabnam Jalilolghadr (Mashhad University of Medical Sciences, 2018)
Background: Congenital hypothyroidism increases the risk of sensorineural hearing loss (SNHL). Children with hearing impairment are prone to communication disorders. The present study aimed to determine the prevalence of SNHL in patients with congenital hypothyroidism in Qazvin, Iran. Methods: This cross-sectional study was conducted on children with transient or permanent congenital hypothyroidism in Qazvin province, Iran in 2015. The patients were identified through national neonatal thyroid screening during 2006-2011. Hearing loss was assessed using the auditory brainstem response (ABR). A minimum of three years of follow-up was carried out to determine the permanency of congenital hypothyroidism. Data analysis was performed using t-test and Chi-square. Results: In total, 155 children with congenital hypothyroidism were enrolled in the study, including 67 females (43.2%) and 151 cases of primary congenital hypothyroidism. Abnormal ABR was observed in 10 patients (6.45%) (6.6% in permanent cases and 6.1% in transient cases), seven of whom were female. In addition, eight patients with primary congenital hypothyroidism and two patients with central congenital hypothyroidism had abnormal ABR (P=0.165). Mean primary thyroid-stimulating hormone levels (52.45±39.91 versus 38.23±28.03 IU/l; P=0.355) and T4 (6.07±4.33 versus 6.98±3.40 µg/dl; P=0.307) had no significant differences in the children with SNHL and other patients. At the beginning of the treatment, mean age of the children with SNHL was 28.50±22.13 days, while it was 28.87±30.34 days in the other subjects (P=0.909). Conclusion: According to the results, the prevalence of SNHL was lower in the patients with congenital hypothyroidism compared to the reported rates in other countries. However, the assessment of hearing loss should be prioritized in the infants with congenital hypothyroidism.